2007
DOI: 10.1167/iovs.06-0892
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Dysfunction in Diabetic Ren-2 Rats Is Ameliorated by Treatment with Valsartan but Not Atenolol

Abstract: These findings suggest that hypertension induces retinal dysfunction that is exacerbated with diabetes and ameliorated by treatment with an AT1-RB, and not just by normalizing BP. These data provide further evidence for the importance of the renin-angiotensin system in development of diabetic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 56 publications
(56 reference statements)
4
44
0
Order By: Relevance
“…ACE inhibition and ARB improve aspects of neuronal and glial damage in both situations [42], such as ameliorating losses in the electroretinogram [25,38,43] and neuronal and glial cell degeneration [44][45][46]. Our identification of renin in retinal Müller cells [2] and ganglion cells [3] is suggestive that aliskiren may influence these cell populations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…ACE inhibition and ARB improve aspects of neuronal and glial damage in both situations [42], such as ameliorating losses in the electroretinogram [25,38,43] and neuronal and glial cell degeneration [44][45][46]. Our identification of renin in retinal Müller cells [2] and ganglion cells [3] is suggestive that aliskiren may influence these cell populations.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are consistent with our previous studies in diabetic Ren-2 rats where we compared ARB with the β-blocker, atenolol. Both treatments normalised BP in diabetic Ren-2 rats; however, only ARB reduced retinal vasculopathy and improved the electroretinogram [24,38]. Similar comparisons in OIR may not necessarily be informative given that β-blockers have anti-proliferative effects in OIR [39], and whether this occurs by a BPdependent mechanism is uncertain as BP cannot be measured in P18 rodents.…”
Section: Discussionmentioning
confidence: 99%
“…26 Given these findings, it was not surprising that valsartan had no effect on the ERG and p-ERK1/2 in shams and improved p-ERK1/2 in OIR. It might be expected that valsartan would restore the ERG in OIR; however, this was unlikely given that although improvements in individual neuronal and glial cell populations can occur in OIR, recovery of overall retinal function can take much longer than the P18 time frame of the present study.…”
Section: Wilkinson-berka Et Al (Pro)renin Receptor and Retinopathymentioning
confidence: 99%
“…Increasing evidence has suggested the contribution of the RAS to diabetes-induced retinal vascular complications including leukocyte adhesion (4), hyperpermeability (11), and impaired blood flow (12); however, little is known about the pathogenesis of angiotensin II-mediated neuronal dysfunction in the diabetic retina. Although AT1R blockade led to amelioration of hypertension-induced retinal dysfunction that was exacerbated with diabetes (13), no data have been reported that show the direct effect of AT1R signaling on diabetes-induced retinal dysfunction together with underlying molecular mechanisms.…”
mentioning
confidence: 99%